1972
DOI: 10.1063/1.1654090
|View full text |Cite
|
Sign up to set email alerts
|

Use of an Electron Flood Gun to Reduce Surface Charging in X-Ray Photoelectron Spectroscopy

Abstract: A flood-gun arrangement is shown to be useful in alleviating the sample-charging problem in x-ray photoelectron spectroscopy. Modest currents (<10−8 A) of low-energy electrons result in the shifting of photoelectron energy peaks to the proper positions and the reduction of the peak widths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

1979
1979
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(17 citation statements)
references
References 1 publication
0
9
0
1
Order By: Relevance
“…For the photoelectron spectroscopy analyses on bulk insulator specimens, one has to explore another way. Whereas the neutralization of the photoholes by using an electron flood gun has been a widely adopted tactic for inorganic insulator materials, 107,108 it is hardly applicable to the organic semiconductor samples because the electrons tend to bring about the chemical degradation in these materials as mentioned above. Zimmermann et al attempted the ARUPS measurements on the single crystal perylene with a compensation of the photoholes by thermionic electrons from a LaB 6 filament equipped nearby the crystal, which was not succeeded in obtaining reasonable ARUPS spectra.…”
Section: Methods Of Overcoming Sample Charging Of An Electrical Insulamentioning
confidence: 99%
“…For the photoelectron spectroscopy analyses on bulk insulator specimens, one has to explore another way. Whereas the neutralization of the photoholes by using an electron flood gun has been a widely adopted tactic for inorganic insulator materials, 107,108 it is hardly applicable to the organic semiconductor samples because the electrons tend to bring about the chemical degradation in these materials as mentioned above. Zimmermann et al attempted the ARUPS measurements on the single crystal perylene with a compensation of the photoholes by thermionic electrons from a LaB 6 filament equipped nearby the crystal, which was not succeeded in obtaining reasonable ARUPS spectra.…”
Section: Methods Of Overcoming Sample Charging Of An Electrical Insulamentioning
confidence: 99%
“…This had the effect of reducing the A1 2p binding energy to values closer to the reference binding energy though there was some sample charging still present (-1 eV) in some of the samples. Using low-energy electrons from an electron flood gun does not only allow correction of the peak positions for charging but gives the additional advantage of decreasing the peak broadening (18). It was found that in the case of the blank alumina the Al 2p peak was present at 74.6 e V after the charge neutralizer was turned on.…”
Section: (C) X-ray Photoelectron Spectroscopy (Xps)mentioning
confidence: 99%
“…This problem however can be easily remedied using an electron flood gun mounted in the HIM chamber. Electron flood guns have been used to reduce surface charging in X‐ray photoelectron spectroscopy (Huchital and McKeon, ), focused ion beam (Utlaut, ), and secondary ion mass spectrometry (Gilmore and Seah, ) techniques for many years. In HIM, an integrated electron flood gun can be used to deliver a diffuse beam of low‐energy electrons to the area being imaged between successive scans (or lines of a scan).…”
Section: Introductionmentioning
confidence: 99%